N‐(3, 4‐dimethoxyphenethyl)‐6‐methyl‐2, 3, 4, 9‐tetrahydro‐1H‐carbazol‐1‐amine inhibits bladder cancer progression by suppressing YAP1/TAZ. (22nd August 2022) - Shiraishi, Yusuke; Maehama, Tomohiko; Nishio, Miki; Otani, Junji; Hikasa, Hiroki; Mak, Tak Wah; Sasaki, Takehiko; Honma, Teruki; Kondoh, Yasumitsu; Osada, Hiroyuki; Yoshida, Minoru; Fujisawa, Masato; et al.
Abstract: Bladder cancer (BlC) is the fourth most common cancer in males worldwide, but few systemic chemotherapy options for its effective treatment exist. The development of new molecularly‐targeted agents against BlC is therefore an urgent issue. The Hippo signaling pathway, with its upstream LATS kinases and downstream transcriptional co‐activators YAP1 and TAZ, plays a pivotal role in diverse cell functions, including cell proliferation. Recent studies have shown that overexpression of YAP1 occurs in advanced BlCs and is associated with poor patient prognosis. Accessing data from our previous screening of a chemical library of compounds targeting the Hippo pathway, we identified DMPCA ( N ‐(3, 4‐dimethoxyphenethyl)‐6‐methyl‐2, 3, 4, 9‐tetrahydro‐1 H ‐carbazol‐1‐amine) as an agent able to induce the phosphorylation of LATS1 and YAP1/TAZ in BlC cells, thereby suppressing their viability both in vitro and in mouse xenografts. Our data indicate that DMPCA has a potent anti‐tumor effect, and raise the possibility that this agent may represent a new and effective therapeutic option for BlC. Abstract : DMPCA decreases YAP1 activity and represses human bladder cancer cell growth in vivo.